MENGKAJI ULANG MEKANISME PENYUSUNAN RENSTRA DAN LAKIP DI DAERAH (Studi Terhadap Persepsi Pejabat Struktural Mengenai Inpres 7 Tahun 1999 dan Keputusan Kepala LAN Nomor 239 Tahun 2003)1 - Baban Sobandi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Indonesian government has responded to various released planning documents, which in practice often overlapped with one another, through Law No. 25 Year 2004.Despite insignificant change in the approach engaged, the current planning seems tobe more systematic and well ordered in terms of the mechanism, nomenclature, andquantity of documents. In this case, several planning documents have been adjustedand simplified. However, one tickling question arises as to whether the mechanism for the formulation and substance of Strategic Planning and LAKIP (GovernmentInstitution Performance Accountability Report) documents are still relevant. Thereview on this matter shows that, in several aspects, there should be adjustments,such as regarding the needs for better understanding and commitment of structuralofficials toward the policy, the choice for target indicators and activities, as well as the mechanism to measure.